Clinical and morphological features actinic keratosis - O. Bondar (Journal of Education, Health and Sport)
The article presents the clinical and morphological characteristics of different variants of actinic keratosis in 20 patients. It was found that in 18 (90.0%) patients, lesions were localized exclusively to exposed skin areas (face, neck, and back of the hands), while in 2 (10.0%) cases, the rash also appeared on the upper and lower extremities and back. The average patient age was 66.5±3.4 years. Morphologically, 7 cases of hypertrophic, 9 cases of atrophic, and 4 cases of Bowenoid actinic keratosis were diagnosed. The Bowenoid type showed no histological differences from Bowen’s disease. Regardless of the histological variant, the dermis exhibited basophilic collagen degeneration and a dense inflammatory infiltrate, predominantly consisting of lymphocytes.